2014
DOI: 10.1177/0363546514540272
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Platelet-Rich Plasma on Muscle Contusion Healing in a Rat Model

Abstract: Before PRP can be recommended for the treatment of muscle contusion injuries, further translational and clinical investigations need to be performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 27 publications
3
52
0
1
Order By: Relevance
“…Platelet poor plasma (PPP) and platelet rich plasma (PRP) were prepared from whole blood under sterile conditions. As no widely used, commercially available clinical system is available to prepare PRP from rats, a manual preparation approach modified from previous studies 1,11 was used. Briefly, blood was centrifuged at 500 × g for 5 minutes at 4°C, followed by a 5 minute rest period, and then another cycle again at 700 × g for 17 minutes at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Platelet poor plasma (PPP) and platelet rich plasma (PRP) were prepared from whole blood under sterile conditions. As no widely used, commercially available clinical system is available to prepare PRP from rats, a manual preparation approach modified from previous studies 1,11 was used. Briefly, blood was centrifuged at 500 × g for 5 minutes at 4°C, followed by a 5 minute rest period, and then another cycle again at 700 × g for 17 minutes at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Clinical studies have shown variable results, 2,16,18,28,30 and basic science and animal studies range from positive outcomes 11,20,25,35 to suggesting little benefit for some types of injury. For example, a recent article by Delos et al 8 showed no benefit of using PRP in an animal model of contusion injury. There are many potential causes for the variation, such as the amount of PRP, concentration of PRP, and timing of PRP administration.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the effect of a series of PRP injections on isometric torque muscle strength in rats. Delos et al found no difference in muscle strength at any time point and no difference in the number centronucleated fibers or inflammatory cells compared to control rodents injected with saline [42]. Hammond et al found no difference in strength for single muscle contraction injuries treated with PRP [43].…”
Section: Treatments To Enhance Return To Sports After Muscle Injurymentioning
confidence: 99%